Multiferroic and magnetoelectric properties of BiFeO3-CoFe2O4-poly(vinylidene-flouride) composite films. (June 2017) - Adhlakha, Nidhi; Yadav, K.L.; Truccato, Marco; Manjusha,; Rajak, Piu; Battiato, Alfio; Vittone, Ettore
Graphical abstract: Highlights: Significant low value of dielectric loss (∼0.05) and AC conductivity (5.9 × 10 −8 Ω −1 cm −1 ) has been observed for the (1 − x )(0.3CoFe2 O4 -0.7BiFeO3 )- x Polyvinylidene difluoride composite film with x = 0.40. A notable increase in saturation (2Ms ) and remnant magnetization (2Mr ) has been observed in electrically poled composite film (with x = 0.30) which shows the presence of strong magnetoelectric coupling in the composite films. A strong room temperature magnetoelectric effect with magnetoelectric voltage coefficient ( αME ) ∼ 22.128 mV/cm Oe has been observed for composite film with x = 0.40, which is possibly a consequence of improved displacement transfer capability of flexible PVDF matrix. Hence these nanocomposite films hold a great potential to be promising candidates for multiferroic devices. Abstract: Multiferroic thick nanocomposite films of (1 − x )(0.3CoFe2 O4 -0.7BiFeO3 )- x Polyvinylidene difluoride (CFO-BFO/PVDF) with x variations 0.20, 0.30 and 0.40 were synthesized using hot press method. Detailed measurements of structural, dielectric, magnetic and magnetoelectric data have been reported. Structural characterization reveals the presence of all the three distinct phases viz. CFO, BFO and PVDF. The dielectric loss as low as 0.05 has been observed for composite film with 40 mol% of PVDF. The AC conductivity (5.9 × 10 −8 Ω −1 cm −1 ) of composite film ( x = 0.40) is found to be much lower as compared to CFO-BFO ceramic. The electric poling of composite film (with x = 0.30) leads to substantial increase in saturation (2Ms ) and remnant magnetization (2Mr ). A significant magnetoelectric effect with magnetoelectric voltage coefficient ( α ME ) ∼ 22.128 mV/cm Oe has been observed for composite film with x = 0.40, which is possibly a consequence of implicit mechanical interaction between CFO and BFO through PVDF matrix. Hence these nanocomposite films hold a great potential to be promising candidates for multiferroic devices.